Plant integrated proportional integrating based control design for electric vehicle charger. (January 2023) - Kumar Seth, Aakash; Singh, Mukhtiar
Highlights: This manuscript presents the control development of ON board EV charger. The paper presents novel controller architecture based on PIPI control. The charger can work under eight operating modes. It can work under active as well as reactive operation. Comparison between PR and PIPI has been presented. The charger is simulated in MATLAB/Simulink environment. The results are analyzed on the basis of transient and steady state response of controller. To validate the claims, hardware prototype is also developed in laboratory using dSPACE 1104. Abstract: The paper presents the control design of on-board two-stage electric vehicle (EV) charger. The first stage AC-DC converter of EV charger plays a very important role in supporting the grid reactively. Therefore, a reduced order plant integrated proportional integrating ( PIPI ) controller has been designed for first stage of EV charger. Generally, a proportional resonant ( PR ) regulator is used for tracking of grid current reference in control of AC-DC converter. However, conventional PR regulator is a third order system due to that the complexity of controller is increased. To reduce the complexity of controller, a first order PIPI regulator has been designed which has all the functionalities of conventional PR regulator and can track any periodic signal. This method is implemented in inner current control loop of first stage AC-DC converter. This results the reduction in controller complexity and better dynamic response as compared with conventional PR regulator. Graphical abstract: Image, graphical abstract